Smoking habits and benign prostatic hyperplasia: A systematic review and meta-analysis of observational studies. Issue 32 (August 2016) - Xu, Huan; Fu, Shi; Chen, Yanbo; Chen, Qi; Gu, Meng; Wang, Zhong
Abstract : Abstract: Previous studies have warned against the promoting effects of cigarette smoking on benign prostatic hyperplasia (BPH). In contrast, some have argued that smoking confers a protective effect regarding BPH, while others have observed an aggravated effect. Thus, we performed this meta-analysis to determine whether cigarette use is associated with BPH risk. To identify articles from observational studies of relevance, a search was performed concurrent to March 21, 2016, on PubMed, Web of Science, Cochrane, EBSCO, and EMBASE databases. Random-effect model, according to the heterogeneity, was calculated to reveal the relative risks (RRs) and corresponding 95% confidence intervals (CIs). Eight articles were included in this meta-analysis, representing data for 44, 100 subjects, of which 5221 (11.8%) had BPH as defined according to the criteria. Seven reports are concerned with analysis between nonsmokers and ex-smokers, in which no significant difference was observed (RR = 0.99, 95% CI 0.94–1.05). Another meta-analysis of 7 studies indicated an observable trend, but without significant difference between groups of nonsmokers and current smokers (RR = 1.17, 95% CI 0.98–1.41). Between groups of heavy (6 articles; RR = 1.02, 95% CI 0.84–1.24) and light smokers (5 articles; RR = 0.90, 95% CI 0.71–1.15), again no significant difference appears. Finally, we combined individuals as never-smokers and ever-smokers and still found no significant difference between the 2 groups of patients (RR = 1.03, 95% CI 0.92–1.15). Sensitivity analysis was displayed and confirmed the stability of the present results. Combined evidence from observational studies shows no significant association between cigarette smoking and BPH risk, either for ex-smokers or for current smokers. The trend of elevated BPH risk from smoking was observed only in current smokers compared with nonsmokers, while marginal significance was observed in comparing ever-smokers with never-smokers in operative patients with BPH.